Development Of Multicultural-Based Interactive Multimedia To Improve Critical Thinking Abilities And Love For Country Of Grade V Students - Padhilah, Muhammad Fitri; Sartono, E. Kus Eddy (Jurnal Mamangan, 2023)
This research aims to: 1) Describe the steps for developing multicultural-based interactive multimedia to improve critical thinking skills and the character of patriotism 2) determine the feasibility of multicultural-based interactive multimedia in improving critical thinking skills and fostering love for the homeland among fifth-grade students, as assessed by material and media experts; 3) assess the practicality of multicultural-based interactive multimedia in enhancing critical thinking skills and patriotism among fifth-grade elementary school students, based on teacher and student responses; and 4) evaluate the effectiveness of multicultural-based interactive multimedia in enhancing critical thinking skills and patriotism in fifth-grade elementary school students. This research was conducted in the South Tapin District, Tapin Regency, South Kalimantan Province, following the 10 steps of the Borg and Gall model. The test subjects comprised 6 students in the limited field test stage, 28 students in the main field test stage, and during the operational field test stage, 23 students in the experimental class and 20 students in the control class. Data were collected through interviews, questionnaires, scales, and tests. Data analysis utilized both qualitative and quantitative methods. Qualitative data were obtained from the results of a preliminary study, while quantitative data were gathered from need analysis interviews, expert assessment scales, teacher and student response questionnaires, test questions, and love of the country questionnaires. An expert assessment scale was employed to determine feasibility, and the analysis involved score conversion into five categories. User response questionnaires were used to evaluate the practicality of multicultural-based interactive multimedia. The effectiveness of multicultural-based interactive multimedia in enhancing critical thinking skills and patriotism was analyzed using N-gain scores, t-tests, and MANOVA tests, with a significance level of 0.05 . (3) multicultural-based interactive multimedia meets practicality criteria based on teacher and student response questionnaires in limited field tests, main field tests, and operational field tests, all rated as "very practical"; (4) the developed multicultural-based interactive multimedia was deemed effective in enhancing the understanding of science concepts and scientific attitudes among fifth-grade elementary school students. MANOVA test results indicate that multicultural-based interactive multimedia significantly improves critical thinking skills and patriotism among fifth-grade elementary school students, with a significant value of p ≤ 0.05.